Pengaruh Persepsi Pendidikan, Upah, Umur Terhadap Produktivitas Tenaga Kerja Shuttlecock Astra Surabaya: Pengaruh Persepsi Pendidikan, Upah, Umur Terhadap Produktivitas Tenaga Kerja Shuttlecock Astra Surabaya - ilham, Mohammad Ilham Ardiansyah; Perdini Fisabilillah, Ladi Wajuba (Universitas Negeri Surabaya, 2025)
Abstract One of the worlds of entrepreneurial issues in Indonesia that has not been resolved is about labor productivity. The study aims to analyze the factors causing the perception of labor productivity to be influenced by perceptions of education, wages, and age. This study uses a quantitative method managed by SPSS assistance. This study was conducted at the Shuttlecock Astra industry in Surabaya, East Java. The type of data used is primary data collected through questionnaires distributed to Shuttlecock Astra employees. The results of the study indicate that perceptions of labor productivity are significantly influenced by perceptions of wages. Conversely, perceptions of education and age are not significantly influenced by perceptions of labor productivity. Keywords: Perception of Education, Perception of Wages, Perception of Age, Perception of Labor Productivity